Development of a Modern Smart Agricultural System Based on IoT and Artificial Intelligence - Denny Irawan; Shofitri Juliana Setiyohadi; Dewi Dewanti Subrata (PT. Global Research Collaboration, 2026)
Abstract – Modern agriculture faces challenges in increasing productivity, efficiency, and sustainability, especially in horticultural commodities such as chilies that have high economic value. The efficiency in question includes the use of increasingly limited land for urban communities. This study proposes the integration of specific multisensor for comprehensive soil parameter monitoring with adaptive decision-making algorithms for chili cultivation in narrow urban areas. The Internet of Things (IoT) is used to monitor environmental conditions in real-time, such as temperature, soil moisture, pH, and nutrient levels (Nitrogen, Phosphorus, and Potassium), through sensors integrated with a wireless network based on the Blynk application and a camera module for early detection of diseases and pests. The collected data is then analysed and processed by a microcontroller using a precise Artificial Intelligence (AI) algorithm, namely the Fuzzy Logic algorithm, to monitor and control land conditions. The integration of IoT and AI is able to increase the efficiency of water and fertilizer use up to 90% of the standard, reduce the risk of crop failure, and improve the quality of chili production results where on the 90th day, chili plants have begun to bear fruit with a fruit diameter at the base of more than 1 cm, a fruit length of more than 3 cm, a stem diameter at the base of about 1 cm, many branches and dense leaves. Compared to conventional agricultural systems, the relevance obtained for urban farmers is: democratization of precision agriculture, optimization of operational costs, real-time risk mitigation, and independent food security. The novelty of this research is the use of adaptive AI Fuzzy Logic, and the integration of visual detection (camera) in one urban ecosystem resulting in high water and fertilizer use efficiency and providing a new contribution in the form of democratization of precision agriculture where industrial-level technology is simplified into a modular ecosystem that is affordable for urban communities. The system that has been built has a structure that allows for development to a broader level including: a modular ecosystem, commodity adaptability, cloud and big data integration, and the potential for vertical farming.